Gender differences in perioperative complications following carotid endarterectomy: A retrospective analysis - Abdullah Burak Balci; Omer Faruk Rahman; Hasan Tezcan; Suleyman Yazici; Nihan Kayalar (Turkish Journal of Vascular Surgery)
Aim: This study aims to examine the distribution of major complications in patients undergoing carotid endarterectomy (CEA) based on gender. The primary objective is to assess the potential effects of gender on perioperative events in hospital. Material and Methods: At Başakşehir Cam and Sakura City Hospital, patients aged 18 and over who underwent CEA between September 2020 and November 2023, were retrospectively analyzed. The patients were categorized into two groups based on their gender. Patient characteristics were obtained from electronic medical records. Postoperative stroke, surgical revision, hematoma, and nerve injury were defined as perioperative events. Results: In this study, the average age of the 225 evaluated patients was found to be 65.8 ± 8.89. There were 73 female patients (32.44%) in Group 1 and 152 male patients (67.56%) in Group 2. Two patients (0.9%) experienced a stroke during the perioperative period. Hematomas were present in 24 patients (10.7%), and nerve damage was also observed in 15 patients (6.7%). Surgical revision due to bleeding was required in thirteen patients (5.8%). Perioperative events were observed in 27 patients. Perioperative events were significantly higher in men than in women (p=0.037). In multivariate logistic regression analysis, male gender was found to be the predictor of perioperative events (odds ratio [OR]: 3.701;95% CI: 1.145-11.963, p=0.029). Conclusion: Our results showed that male gender may be a predictor of perioperative events in patients undergoing carotid endarterectomy. Multicenter and larger study groups may be needed for healthier results. [Turk J Vasc Surg 2024; 33(3.000): 146-51]